Factors that affect employee’s productivity in Pusat Pungutan Zakat Wilayah Persekutan (PPZ-MAIWP) / Nurul Izyan Zainal Rashid - Zainal Rashid, Nurul Izyan (Faculty of Business and Management, 2013)
The exploratory study focused on the factors that affect employee’s productivity in Pusat Pungutan Zakat Wilayah Persekutuan Kuala Lumpur (PPZ-MAIWP). These studies focus on ineffective of zakat collection centres. Purpose of this research is to investigate factor (stress, employee satisfaction, financial behavior and health condition) that contribute towards employee productivity and to ascertain the best predictor that influence productivity. The research involved 102 workers which randomly chosen in Pusat Pungutan Zakat Wilayah Persekutuan Kuala Lumpur (PPZ-MAIWP) as a sample. The findings and analysis based on data obtained from questionnaire responses. SPSS 16.0 are used to analysing data and method used is Cronbach’s Alpha to measure the reliability of data and descriptive statistic that consist of frequency distributions and hypothesis testing which consist of Pearson Correlation Matrix. From the finding, it can be concluded that financial behavior problems, employee satisfaction and health condition among employee lead to unproductive. While employee stress is not factor affect employee productivity in Pusat Pungutan Zakat Wilayah Persekutuan (PPZ-MAIWP).